Evaluation of User Acceptance and Experience of the Coretax System Among Corporate Taxpayers in Indonesia - Rahmah, Khairunnisa; Yansyah, Deli; Prabowo, Agung (STMIK Widya Cipta Dharma, 2025)
The rapid digital transformation in public administration has encouraged the Direktorat Jenderal Pajak (DJP) of Indonesia to implement the Coretax system as part of its modernization agenda for tax administration. This study aims to evaluate the level of user acceptance and experience of the Coretax system among corporate taxpayers in Indonesia using the Technology Acceptance Model (TAM) approach. The research focuses on examining the relationships between perceived ease of use (PEOU), perceived usefulness (PU), behavioral intention (BI), and use behavior (UB), with an additional variable (usage barriers) to explore external factors that may hinder technology adoption. The study employed a quantitative method involving a survey of 136 corporate taxpayers who actively use Coretax. Data were analyzed using descriptive statistics, regression analysis, and mediation testing through the PLS-SEM approach. The results indicate that all primary hypotheses (H1–H5b) are significantly supported (p < 0.05). PU emerged as the most dominant factor influencing BI and UB, while PEOU plays a significant role in shaping PU and BI. Behavioral intention acts as a full mediator between users’ perceptions and actual usage behavior. Moreover, perceived usage barriers negatively affect both PEOU and BI. These findings validate TAM within the Indonesian digital taxation context and highlight that successful Coretax implementation depends not only on system usability and benefits but also on continuous technical support and user training to ensure a positive digital experience.